Analysis Of The Differences In Real Rates And Ina-Cbgs Rates In Delivery Case Of Inpatible Patients For Cost Control At Pandan Arang Boyolali Hospital - Sutrisno, Bowo (Indonesian Journal of Health Information Management, 2023)
Abstract The hospital will get payment based on the INA-CBG's rate which is the average cost spent by a diagnosis group. Childbirth is a process of expelling the products of conception (fetus and placenta) which are of sufficient gestational age and can live outside the womb through the birth canal or other means with the help or strength of the mother herself.The difference in real rates and INA-CBG's rates in cases of inpatient delivery at Pandan Arang Boyolali Hospital can result in hospital losses. This study aims to determine the difference between real rates and INA-CBG's rates in cases of inpatient delivery at Pandan Arang Boyolali Hospital. This type of research is analytic observational with a comparative approach. The population in this study were all medical record files of inpatients for delivery cases at Pandan Arang Boyolali Hospital in the second quarter of 2022, totaling 242 patients. The sampling technique is simple random sampling. Data analysis used the Mann Whitney test. The results of this study found that the real rate for inpatient delivery cases at Pandan Arang Boyolali Hospital was Rp. 341.321.130 while the amount of the INA CBGs tariff is Rp. 264.357.400.so it can be concluded that there is a difference in real rates and INA-CBGs in cases of inpatient delivery at Pandan Arang Boyolali Hospital Keywords. Real Tariff, INA CBGs Tariff, Labor